Surgical considerations for neonates with necrotizing enterocolitis. Issue 6 (December 2018) - Hong, Charles R.; Han, Sam M.; Jaksic, Tom
Abstract: Necrotizing enterocolitis (NEC) is a potentially devastating condition that preferentially affects premature and low birth weight infants, with approximately half requiring acute surgical intervention. Surgical consult should be considered early on, and deterioration despite maximal medical therapy or the finding of pneumoperitoneum are the strongest indications for emergent surgical intervention. There is no clear consensus on the optimal surgical approach between peritoneal drainage and laparotomy; the best course of action likely depends on the infant's comorbidities, hemodynamic status, size, disease involvement, and available resources. Patients who develop surgical NEC are at a significant risk for morbidity and mortality, with long-term complications including short bowel syndrome, growth failure, and neurodevelopmental impairment. Further research into strategies that optimize outcomes following surgery for NEC in the neonatal intensive care unit and long-term are paramount.